Effects of Mixing Garlic Skin on Fermentation Quality, Microbial Community of High-Moisture Pennisetum hydridum Silage - Chen, Juncai; Huang, Guohao; Xiong, Hanlin; Qin, Hao; Zhang, Haonan; Sun, Yawang; Dong, Xianwen; Lei, Yan; Zhao, Yongju; Zhao, Zhongquan (Frontiers in Microbiology, 2021)
Garlic skin, a by-product of garlic processing, was supposed to improve the fermentation quality of high-moisture silages because of its low moisture content and active compounds. Thus, fermentation and microbial characteristics of high-moisture Pennisetum hydridum ensiled with the addition of 0 wt%, 10 wt%, 20 wt%, and 30 wt% garlic skin (on a fresh matter basis) were analyzed during a 60-d fermentation. Results showed that the addition of garlic skin increased the dry matter content and lactic acid production, and decreased the pH and ammonia-N content of the silage. Adding garlic skin changed the relative abundance of bacterial communities with an increase in Lactobacillus and a decrease in Clostridium relative abundance. In conclusion, co-ensiling of high-moisture Pennisetum hydridum with garlic skin could be a simple approach to improve the silage quality and nutrients preservation.